The efficacy of rapid biophysical profile in predicting poor pregnancy outcomes in suspected intrauterine growth restriction fetuses: preliminary study - Chousawai S. (2014)
Objective: To determine the efficacy of the rapid biophysical profile (rBPP), which includes sound-provoked fetal movement detected by ultrasonography, and amniotic fluid index for antepartum fetal well-being assessment in suspected intrauterine growth restriction (IUGR) fetuses. Material and Method: One hundred seven tests of rBPP were antenatally performed in 30 IUGR fetuses who attended the ANC unit at Maharaj Nakorn Chiang Mai Hospital between October 2009 and July 2010. Pregnancy outcomes were prospectively recorded for subsequent analysis. The accuracy of rBPP was based on poor outcomes including fetal distress, low Apgar score, admission to the neonatal intensive care unit, and perinatal death. Results: In 107 tests, the incidences of negative, equivocal, and positive rBPP were 88.8%, 10.3%, and 0.9%, respectively. There was one adverse pregnancy outcome of intrapartum fetal distress. The rBPP had a sensitivity of 100.0%, a specificity of 89.7%, a positive predictive value of 25%, and a negative predictive value of 100.0%. Conclusion: The rBPP may probably be an effective predictor of poor pregnancy outcome in IUGR fetuses. With its high specificity and rapidity, the rBPP may be used as a back-up test to confirm fetal well-being in pregnancies complicated by IUGR at the antenatal care clinic.